The Complete Guide to Mentoring: How to Design, Implement and Evaluate Effective Mentoring Programmes - Hilarie Owen (UK Kogan Page, 2011)
Mentoring can be a powerful tool in the development of talent within any organization. Experienced colleagues can help build the skills, competencies and confidence of staff, who will go onto to contribute to and drive the success of an organization. In this book, Hilarie Owen explains the skills a mentor needs and how managers can be sure it is having a positive impact. The Complete Guide to Mentoring provides a road map for implementing mentoring programs in an organization. Providing practical guidance on every aspect of the design, implementation and assessment of a mentoring program, it includes a wealth of practical advice and resources including checklists and template forms, which can be downloaded from the publisher's website and used as handouts for both the mentor and mentee. This valuable resource provides a step-by-step guide for anyone who wants to create and run mentoring schemes with confidence and success.
Keywords: Career development; Mentoring; Nonfiction; Leadership and Mentoring (HRM2073-N)